Critical review of literature on behaviour of web tapered built-up sections as beam-column members in pre-engineered steel buildings - Meghrajani, Ramesh Vasudeo; Ingle, R. K. (Journal of Structural Engineering, 2024)
Pre-engineered steel buildings (PEB), increasingly being used for wider applications across India, use 3-plated webtapered sections as mainframe components or primary members, constituting about 50% of the total steel used. With limited guidance available in IS-800:2007, these buildings are modeled in accordance to codal provisions of American Institute of Steel Construction Inc. (AISC) and Low Rise Building Systems Manual, Metal Building Manufactures Association (MBMA). Starting with reference to provisions of IS, study of other codes like British Standards (BS 5950), American Standards (AISC) and Australian code AS-4100 is conducted. Further comprehensive literature review is complied to define behaviour of web-tapered I sections with respect to effective length, section properties and taper ratio to identify modification parameters for axial load capacity and moment of resistance with reference to lateral or flexural torsional buckling.